Endogenous technology, matching, and labor unions: Does low-skilled immigration affect the technological alignment of the host country? - Dario Cords (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
In recent years, Germany and other European countries face the strongest immigration flow in their history. Experts unanimously agree that one of the core factors of a successful social integration is the labor market participation of the new arrivals. This paper investigates the impact of low-skilled immigration on a unionized economy with labor market frictions. It especially examines how immigration affects the technology choice of firms and, thereby, the technological alignment of the host country. The labor market is characterized by heterogeneity on both sides of the market. Within this framework, it can be shown that low-skilled immigration encourages firms to invest more in a basic technology, which leads to a deterioration of the technology level in the whole economy. It can be further shown that policies, which improve the access of already existing low-skilled immigrants to the labor market counteract the effect that is triggered by an increase in low-skilled immigration.
urn:nbn:de:bsz:100-opus-13985
Keywords: F22; J24; J31; J51; J61; J64; 330; Immigration; Technology Choice; Search and Matching; Labor Unions; Skillheterogeneity